Functions of Statistics in the publication of scientific original papers - Soler Cárdenas, Silvio Faustino (Atenas, 2016)
Through this work, the importance of statistical methodology in writing original papers is apparent; in addition, the necessary level of knowledge of the makers in the statistical matter, as a necessary issue of the scientific redaction, is evidenced. It is discussed the fine relation among science, conceived as a direct productive power, the scientific publication and Statistics, pointing out the function of this discipline according to the description of the design of the study, the analysis and explanation of obtained results.